The Relation of Pain and Disability with Radiographic and Pedobarographic Parameters in Adult Pes Planus - Kaan Uzunca,; Nurettin Taştekin,; Murat Birtane, (Archives of Rheumatology, 2006)
Objective: Pes planus is characterized by the absence or collaps of medial longitudinal arc of the foot. Clinically, the pain symptom can be seen while standing and during walking. In this study, we aimed to investigate the relation of foot pain and disability with foot plantar pressure values and radiological findings in adult pes planus patients. Patients and Methods: Thirty patients with pes planus who had foot pain and functional limitations were evaluated by using to the pain and disability sections of “Foot functional index” that are pain and disability sections. The static and dynamic plantar pressure values of all the patients were measured by using pedobarographic investigations. The numeric value of calcaneal pinch angle was measured on lateral foot radiography. The relation of pressure and the calcaneal pinch angle with pain and disability was investigated. Results: Although there was no correlation between pain and disability with pressure values obtained from static evaluation in patients with pes planus (p>0.05), pain was negatively correlated with foot pressures of anterior-lateral and medium region of foot in dynamic evaluation (p<0.05). A positive correlation was found between disability and plantar contact area (p<0.05). Calcaneal pinch angle values were negatively correlated with pain and disability scores (p<0.05). Conclusion: Absence or collapse of medial longitudinal arc in pes planus patients impairs shock absorbance effect of the arc and accompany pain during walking and disability. (Rheumatism 2006; 21: 95-9)